RETHINKING DESIGN EDUCATION: FROM ART TO STRATEGY IN THE NEURAL AGE - Asylkhanov, Ермек (Рroblems of engineering and professional education, 2024)
This article attempts to present a comprehensive model for modernizing educational programs in higher education. The purpose of the work is not to list new trends, but to substantiate and structure the main areas of modernization that will prepare competitive and adaptive specialists ready for the challenges of tomorrow. The author analyzes the shortcomings of existing educational standards and proposes a transition to a predictive learning model aimed at developing competencies that will be in demand in the future within 3-7 years. Currently, the design education system has entered a period of radical transformation under the influence of the development of generative artificial intelligence (AI). Traditional, craft approaches are losing their relevance; specialists are required to have strategic thinking, empathy, and conceptual work. Against the background of these changes, there is a need to revise the content, methodology, and technological base for training future designers. The article presents a comprehensive model for modernizing design education. In this model, AI is organically introduced into all stages of the creative process. Specific didactic units are analyzed, from neural networks such as Midjourney, DALL-E, to the use of AI assistants in UX/UI and motion design. The importance of introducing VR/AR, no-code platforms and digital ethics into the curriculum is also emphasized.